Optimations of Product Combinations with Goal Programming Method - B., Rika N.; Pradjaningsih, Agustina; Dewi, Yuliani Setia (Majalah Ilmiah Matematika dan Statistika, 2015)
Goal programming is linear programming technique which is used to solve problem with some goals. This method used to minimize the undesirable deviation from some targets which want to be reached. The targets expressed in a mathematic equation called constraint function. There are two constraint functions, goal constraint function and structural constraint function. On this paper solution of the optimal product combinations problems will be finded from nata de coco packs which have purpose to minimize ripening and sale maximization.